2002
DOI: 10.1136/pmj.78.925.671
|View full text |Cite
|
Sign up to set email alerts
|

Defensive practice among psychiatrists: a questionnaire survey

Abstract: Objective: There has been little research on the prevalence of defensive practice within hospital settings. The aim of this report was to examine the extent of defensiveness among psychiatrists and to examine the relationship between defensiveness and seniority, as well as the effect of previous experiences on the level of defensiveness. Design: A postal questionnaire survey on defensive practice. Setting: Northern Region of England. Subjects: 154 psychiatrists in the region. Results: 96 responses were receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 13 publications
2
38
2
3
Order By: Relevance
“…Within this climate, there is an argument that psychiatrists respond to uncertainty by practising defensively (Coid & Cordess, 1992) and adopting a conservative approach, defined as preferring to err on the side of caution, overstating rather than understating risk (Perhac, 1996). This has been supported by empirical evidence (Passmore & Leung, 2002), both in general and forensic psychiatry (Webster et al, 1982) and in the broader risk literature, where it has been suggested that a precautionary risk management style is more likely when encountering uncertainty (Klinke & Renn, 2002). Furthermore, such a conservative approach has been associated with the tendency to overpredict violence, which Buchanan (1999: p. 468) suggests may occur, among other reasons, because 'clinicians would rather detain someone who will not be violent than release someone who will be'.…”
Section: Uncertainty and Risk Assessmentsupporting
confidence: 65%
“…Within this climate, there is an argument that psychiatrists respond to uncertainty by practising defensively (Coid & Cordess, 1992) and adopting a conservative approach, defined as preferring to err on the side of caution, overstating rather than understating risk (Perhac, 1996). This has been supported by empirical evidence (Passmore & Leung, 2002), both in general and forensic psychiatry (Webster et al, 1982) and in the broader risk literature, where it has been suggested that a precautionary risk management style is more likely when encountering uncertainty (Klinke & Renn, 2002). Furthermore, such a conservative approach has been associated with the tendency to overpredict violence, which Buchanan (1999: p. 468) suggests may occur, among other reasons, because 'clinicians would rather detain someone who will not be violent than release someone who will be'.…”
Section: Uncertainty and Risk Assessmentsupporting
confidence: 65%
“…Defensive medicine, by definition, is intended for our own benefit and only incidentally, if at all, the patient's. 1,[7][8][9][10][11][12][13][14][15][16] Yet physicians who self-report defensive medical practices do so quite unblushingly and with no sense that their behavior could be challenged as lacking in professionalism. 17,18 They appear not to regard practicing defensively as a choice; rather they appear to see it as being forced upon them by circumstances.…”
Section: Professionalism and Tort Reformmentioning
confidence: 99%
“…En Inglaterra un cuestionario enviado a mé dicos psiquiatras identificó que un 75% de los profesionales había realizado medicina defensiva en el mes anterior 12 . Sin embargo, la actitud defensiva no parece ser la solució n a este problema.…”
Section: Tipo De Profesional Y Tipo De Sentenciaunclassified